Encephalartos villosus Lem. Displays a Strong In Vivo and In Vitro Antifungal Potential against Candida glabrata Clinical Isolates - Moneerah J. Alqahtani; Engy Elekhnawy; Walaa A. Negm; Sebaey Mahgoub; Ismail A. Hussein (Journal of Fungi, 2022)
Recently, Candida glabrata has been recognized as one of the most common fungal species that is highly associated with invasive candidiasis. Its spread could be attributed to its increasing resistance to antifungal drugs. Thus, there is a high need for safer and more efficient therapeutic alternatives such as plant extracts. Here, we investigated the antifungal potential of Encephalartos villosus leaves methanol extract (EVME) against C. glabrata clinical isolates. Tentative phytochemical identification of 51 metabolites was conducted in EVME using LC–MS/MS. EVME demonstrated antifungal activity with minimum inhibitory concentrations that ranged from 32 to 256 µg/mL. The mechanism of the antifungal action was studied by investigating the impact of EVME on nucleotide leakage. Additionally, a sorbitol bioassay was performed, and we found that EVME affected the fungal cell wall. In addition, the effect of EVME was elucidated on the efflux activity of C. glabrata isolates using acridine orange assay and quantitative real-time PCR. EVME resulted in downregulation of the expression of the efflux pump genes CDR1, CDR2, and ERG11 in the tested isolates with percentages of 33.33%, 41.67%, and 33.33%, respectively. Moreover, we investigated the in vivo antifungal activity of EVME using a murine model with systemic infection. The fungal burden was determined in the kidney tissues. Histological and immunohistochemical studies were carried out to investigate the effect of EVME. We noticed that EVME reduced the congestion of the glomeruli and tubules of the kidney tissues of the rats infected with C. glabrata. Furthermore, it decreased both the proinflammatory cytokine tumor necrosis factor-alpha and the abnormal collagen fibers. Our results reveal, for the first time, the potential in vitro (by inhibition of the efflux activity) and in vivo (by decreasing the congestion and inflammation of the kidney tissues) antifungal activity of EVME against C. glabrata isolates.